Do interventions to prevent or stop abuse and neglect among older adults work? A systematic review of reviews. Issue 5 (19th October 2020) - Marshall, Khiya; Herbst, Jeffrey; Girod, Candace; Annor, Francis
ABSTRACT: Abuse and neglect among older adults impact everyone and are recognized internationally as significant and growing public health issues. A systematic review of reviews was conducted to identify effective strategies and approaches for preventing abuse and neglect among older adults. Eligible reviews were systematic or meta-analyses; focused on the older population as reported in the publications; reviewed prevention interventions; included relevant violence and abuse outcomes; written in English; and published in a peer-reviewed journal between January 2000 and May 2020. Eleven unique reviews (12 publications) met the eligibility criteria, including one meta-analysis. Included reviews mainly focused on general abuse directed toward older adults; and educational interventions for professional and paraprofessional caregivers, multidisciplinary teams of health care and legal professionals, and families. Interventions were implemented in a variety of community and institutional settings and addressed primary, secondary, and tertiary prevention. The reviews indicated weak or insufficient evidence of effectiveness in preventing or reducing abuse, yet several promising practices were identified. Future research is needed to evaluate emerging and promising strategies and approaches to prevent abuse among older adults. Effective interventions are also needed to prevent or reduce abuse and neglect among older adults.